The effect of quercetin on microRNA expression: A critical review - Dostal, Zdenek; Modriansky, Martin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
Quercetin, a flavonoid with multiple proven health benefits to both man and animals, displays a plethora of biological activities, collectively referred to as pleiotropic. The most studied of these are antioxidant and anti-inflammatory but modulation of signalling pathways is important as well. One of the lesser-known and recently discovered roles of quercetin, is modulation of microRNA (miRNA) expression. miRNAs are important posttranscriptional modulators that play a critical role in health and disease and many of these non-coding oligonucleotides are recognized as oncogenic or tumor suppressor miRNAs. This review is an evaluation of the recent relevant literature on the subject, with focus on the ability of quercetin to modulate miRNA expression. It includes a summary of recent knowledge on miRNAs deregulated by quercetin, an overview of quercetin pharmacokinetics and miRNA biogenesis, for the interested reader.
Keywords: mikro RNA; microRNA; exprese genu; Gene Expression; Quercetin; expression; MicroRNAs; Animals; lidé; polyphenols; biogenesis; Humans; zvířata; quercetin